2009
DOI: 10.1007/s00464-008-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

When sleeve gastrectomy fails: adding a laparoscopic adjustable gastric band to increase restriction

Abstract: The use of laparoscopic sleeve gastrectomy (LSG) as a procedure for morbid obesity has recently increased. The LSG procedure is used most often as a part of a biliopancreatic diversion with duodenal switch (BPDDS) or as a first stage that can be converted to a BPDDS or Roux-en-Y gastric bypass (RYGB). However, the surgical indications for LSG have rapidly expanded, and some centers use the sleeve as the primary operation for morbid obesity.The utility of LSG as a primary procedure is controversial, with consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…There has been a recent report of using human collagen as a band for sleeve gastrectomy at the primary operation [16]. Greenstein et al [17] recently reported placement of a laparoscopically inserted gastric band around the upper part of the stomach that had a previous sleeve gastrectomy that had become dilated and was associated with poor weight loss. At 9 months, the patient had a 57% loss of excess body weight, suggesting the utility of combining banding with sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent report of using human collagen as a band for sleeve gastrectomy at the primary operation [16]. Greenstein et al [17] recently reported placement of a laparoscopically inserted gastric band around the upper part of the stomach that had a previous sleeve gastrectomy that had become dilated and was associated with poor weight loss. At 9 months, the patient had a 57% loss of excess body weight, suggesting the utility of combining banding with sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In case of failure, conversion to biliopancreatic diversion or RYGB is the next option. Nowadays, usage of gastric band on the remaining gastric tube with success in EBWL has been reported [26,27].…”
Section: Does Size Matter?mentioning
confidence: 99%
“…Removal of the principal site of ghrelin production leads to a decrease in ghrelin levels, adding a hormonal element to SRSG, that other restrictive procedures, such as adjustable gastric banding lack [13]. Some authors have reported the use of added restriction in SG to increase the intensity and duration of weight loss [6,14,15]. In addition, by placing a Silastic® ring around the stomach in all the patients in this study, both procedures were identical in terms of the portion of the stomach located above the ring.…”
Section: Discussionmentioning
confidence: 99%